2017
DOI: 10.1038/s41477-017-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis BTB/POZ protein-dependent PENETRATION3 trafficking and disease susceptibility

Abstract: The outermost cell layer of plant roots (epidermis) constantly encounters environmental challenges. The epidermal outer plasma membrane domain harbours the PENETRATION3 (PEN3)/ABCG36/PDR8 ATP-binding cassette transporter that confers non-host resistance to several pathogens. Here, we show that the Arabidopsis ENDOPLASMIC RETICULUM-ARRESTED PEN3 (EAP3) BTB/POZ-domain protein specifically mediates PEN3 exit from the endoplasmic reticulum and confers resistance to a root-penetrating fungus, providing prime eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…In summary, these data support a dual function of ABCG36 in the polar (rootward) distribution of IBA in the root and local IBA/IAA homeostasis in the very root tip. These features correlate with the mainly polar (lateral) expression pattern in the mature root and a widely non-polar expression in the LR cap cells (see Figure 3D; Strader and Bartel, 2009; Ruzicka et al, 2010; Mao et al, 2016, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…In summary, these data support a dual function of ABCG36 in the polar (rootward) distribution of IBA in the root and local IBA/IAA homeostasis in the very root tip. These features correlate with the mainly polar (lateral) expression pattern in the mature root and a widely non-polar expression in the LR cap cells (see Figure 3D; Strader and Bartel, 2009; Ruzicka et al, 2010; Mao et al, 2016, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…At first, we tested an elicitor prepared from Fusarium oxysporum (Fo), a well-characterized, ubiquitous root vascular fungal pathogen that causes wilt disease on several plant species, including Arabidopsis thaliana (Gordon, 2017). Moreover, we had previously shown that agcg36/pen3 is hypersensitive to Fo infection (Mao et al, 2017b). Like IBA and CLX, Fo elicitor treatment resulted in strong accumulation of ABCG36 but not that of ALK1 (Fig.…”
Section: Abcg36 Is An Exporter Of Camalexin That Functionally Interac...mentioning
confidence: 99%
“…The myrosinase PEN2 and the ABC-transporter PEN3 mediate callose deposition as well, and furthermore control the production (PEN2) and secretion (PEN3) of Trp-derived antimicrobial glucosinolates [46,47]. Both pathways require rather complex activation mechanisms [48,49] but eventually lead to the rapid relocalization of intracellular PEN1 and PEN3 pools to the PM [31]. As both PEN1 and PEN3 participate in fusion processes at the PM during both abiotic and biotic stresses [49], it is still unclear how exactly pathogens manipulate these pathways.…”
Section: The Golgi Apparatus and The Trans-golgi Network/early Endosomentioning
confidence: 99%
“…Both pathways require rather complex activation mechanisms [48,49] but eventually lead to the rapid relocalization of intracellular PEN1 and PEN3 pools to the PM [31]. As both PEN1 and PEN3 participate in fusion processes at the PM during both abiotic and biotic stresses [49], it is still unclear how exactly pathogens manipulate these pathways. One possibility is that the interaction of the B. graminis effector BEC4 with the ARF-GAP AGD5 and an ubiquitin-conjugating enzyme results in degradation of AGD5 [50].…”
Section: The Golgi Apparatus and The Trans-golgi Network/early Endosomentioning
confidence: 99%